Pengembangan Pembelajaran PAI dalam Kurikulum Merdeka Era Digital - Basri, Hasan (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study aims to find out how the development of Islamic religious education learning in the independent curriculum learning the digital era and find out how the problems of learning Islamic religious education in the independent learning curriculum at MTs Negeri 1 Yogyakarta. Data collection in this study used interviews, observation and documentation. The results of this study show that religious education learning in the independent digital era learning curriculum at MTs Negeri 1 Yogyakarta is to provide guidance to students to become individuals who have noble morals and fear Allah Swt. and have the ability to think critically, have the ability to do high activities, be able to communicate well, be able to collaborate and be confident and can utilize technology as a learning medium for Islamic religious education. As for the problems of learning Islamic religious education in the independent learning curriculum in the digital era, namely: human resources are not adequate to implement Islamic religious education learning in the digital era, PAI teachers have not mastered the concept of an independent learning curriculum and do not have qualified abilities in using technological media in learning, low quality of education, inadequate facilities and infrastructure. So the solution that can overcome the problems of learning Islamic religious education in the digital era is to develop and improve human resources first, provide facilities and infrastructure and utilize technological media in learning Islamic religious education.